Alternative hypotheses regarding the association between early engagement in gambling and gambling‐like activities and later problem gambling – a commentary on Richard and King (2023). (31st January 2023) - Rhee, Soo Hyun; Ellingson, Jarrod M.
Abstract : This issue of the Journal of Child Psychology and Psychiatry includes a systematic review on the emergence of problem gambling from childhood to emerging adulthood (Richard & King, 2023). The importance of understanding the risks for problem gambling earlier in development is clear, given the increasing availability of gambling to minors, especially online gambling.